Artificial Bee Colony Optimization Algorithm for Uncapacitated Facility Location Problems. - Tuncbilek, Nukhet; Tasgetiren, Fatih; Esnaf, Sakir (Journal of Economic & Social Research, 2012)
In this paper, a new multiple facility location and allocation method is proposed. This algorithm assigns demand points to pre-determined facilities which have infinite capacities, by using an artificial bee colony optimization with local search to solve discrete uncapacitated multiple facility location problems. This method is tested and compared with continuous and discrete particle swarm optimization based facility location methods on alternative models with or without local search for optimizing the well-known benchmark problems and generated problems.Similar test is conducted on actual demand and transportation cost data from a fertilizer manufacturer from Turkey, which includes 11 facility locations and 768 demand points. Proposed ABC-based algorithm exhibited better performance than the PSO-based algorithms.